Da’wah Communication Strategy of Kiai Marogan Islamic Boarding School Palembang in the Mass Media - Muslimin Muslimin; Sri Hertimi (Fakultas Dakwah dan Komunikasi, Universitas Islam Negeri, Raden Fatah Palembang, 2023)
The purpose of this research is to find out how the da'wah communication strategy is implemented in the Kiai Marogan Islamic boarding school in the mass media. Next, to find out what factors that support and barricade the Da’wah program in Kiai Marogan Islamic boarding school. Therefore, the objectives of this study are first, to find out how the da'wah communication strategy is implemented in the Kiai Marogan Islamic boarding school in the mass media. Second, to find out the community's responses to the development of the Kiai Marogan Islamic boarding school. Third, this research can be a reference in making new policies for the development of da'wah programs. Whereas the benefits of this research first, theoretically, the results of this research can add to the repertoire of da'wah and the communication field. Second, practically, the results of this research are expected to give a positive contribution to da'wah activists, both individually, in groups, institutions, organizations, and the government in formulating the most appropriate strategy to overcome the problems in da'wah. This study uses a qualitative method, which aims to understand in depth the phenomenon in da'wah communication which occurs in Kiai Marogan Islamic boarding school.